2006
DOI: 10.1089/ten.2006.12.2649
|View full text |Cite
|
Sign up to set email alerts
|

Two Techniques for the Preparation of Cell-Scaffold Constructs Suitable for Sinus Augmentation: Steps into Clinical Application

Abstract: The objective of this clinical trial was the analysis of 2 methods for engineering of autologous bone grafts for maxillary sinus augmentation with secondary implant placement. Group 1 (8 patients, 12 sinuses): cells of mandibular periosteum were cultured in a good manufacturing practice laboratory (2 weeks) with autologous serum and then transferred onto a collagen matrix. After another week, these composites were transplanted into the sinuses. In group 2A (2 patients, 3 sinuses), cells of maxillary bone were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…With clinical application in mind, we limited the cell characterization studies to <8 culture passages, when the cultures reached sufficient cell numbers for the preparation of TE-bone substitutes [41]. Currently, most clinical study protocols involve the use of early (<5) passage cells, to minimize the changes associated with in vitro cultivation [29], [30], [31], [47], [48], [49]. However, to fully utilize the primary alveolar bone cells as an in vitro model, the phenotype and proliferation of cells in later passages should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With clinical application in mind, we limited the cell characterization studies to <8 culture passages, when the cultures reached sufficient cell numbers for the preparation of TE-bone substitutes [41]. Currently, most clinical study protocols involve the use of early (<5) passage cells, to minimize the changes associated with in vitro cultivation [29], [30], [31], [47], [48], [49]. However, to fully utilize the primary alveolar bone cells as an in vitro model, the phenotype and proliferation of cells in later passages should be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to several clinical reports where periosteal cells were harvested specifically for the purpose of TE-bone substitutes preparation [31], [47], [48], [49], our approach involves the use of bone tissue remnants, obtained during routine periodontal surgical procedures, as a source of osteogenic cells, thus avoiding additional injury to patient due to tissue harvesting. A few prior studies reported clinical application of TE-bone substitutes derived from alveolar bone cells [29], [30], [31], [50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations